Newspaper Citations in Scientific Publications Indexed in Web of Science (2001-2010) - Jeevan Singh, Angom; Ravikumar, S. (Journal of Information and Knowledge, 2021)
The objective of the paper is to find out the citations of newspapers in scientific publications during 2001-2010. The study was carried out for twenty English newspapers indexed in Web of Science with 250 or more citations up to 31st December, 2015. For the present study only newspaper articles of these twenty newspapers with 2 (two) or more citations were considered. During the study period there were 4146 records (newspaper articles) with 13250 citations in different scientific publications. The citations to these news paper articles in scientific publications increased gradually from 2006 onwards. These newspaper articles were highly cited in Fordham Law Review (USA) with 160 (1.21%) citations followed by American Journal of International Law (USA) with 138 (1.04%) citations.